Fighting Gender-Based Violence With Feminist Art Pedagogy: A Co-Choreography Between Teacher, Students, and Anonymous Activists - Bilodeau, Annik; Wilson, Ariane M (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2025)
Activist groups like No Estamos Todas (NET) leverage social media to share art memorializing feminicide victims. While analyzing NET’s social media posts for patterns in representations of victims, we noticed contributions starting in 2017 from middle schoolers in Illinois. The way these artworks focus on victims’ lives led us to explore a collaboration between NET, these students, and their teacher. Through a feminist pedagogical analysis of the project, we argue that the students engage in recognition-based gender justice. We provide guidelines for implementation and pedagogical approaches, hoping to inspire teachers to recognize students as agents of change.